Определение энергосберегающего потенциала на действующих предприятиях производства жиров - Товажнянский, Леонид Леонидович; Капустенко, Пётр Алексеевич; Ульев, Леонид Михайлович; Болдырев, Станислав Александрович (НТУ "ХПИ", 2007)
It is shown, that economic potential of energy saving, accessible to processes integration of the examined fat plant is equal 232 thousand dollars of the USA that makes 76 % of cost of the energy consumed working processes without consideration of other consumers, and 15 % of cost of the energy consumed by factory.
Keywords: пищевая промышленность; теплообменники; экстракция данных